Ética e serviço social: análise dos valores que norteiam os laudos sociais nas ações de guarda das varas de família do tribunal de justiça de Minas Gerais - Pereira, Carla Alexandra (2008)
This dissertation was designed to analyze social reports written by professional social workers who are employed by Family Court Divisions of Minas Gerais State Court of Justice (Tribunal de Justiça de Minas Gerais - TJMG), from the perspective of 1993 Ethical Code of Social Workers values and ethical principles. Particularly in TJMG, Family Court Divisions demanded written Social Studies and Investigations of social workers. Those professionals are commissioned as State Representatives to implement an intervention in family environment. Such intervention intends to produce a technical document (Social Study or Social Report) that must be able to support judicial decisions, as an expert analyses recommending whether is possible or not to concede a custody petition. In this way, social study reports need to demonstrate some aspects and determinants about social and family life of all those involved in law action, as: intrafamily relationship (affective links, socialization processes and potential physical and psychological violence occurrences); social questions those would be identified as family conflict causes or social questions those would can still provoking it; social relationships of family group and their general social and economical conditions. This research demanded closest approximation of this kind of social worker instrument of communication in the forensic universe and it had written keeping in mind how it could contribute to professional usage in this specific area. However, this research does not restrict itself on what those professionals have showed in their discourses about values, but it has driven itself through ethical commitment to the users that are involved on the intervention process and social report. From this assumption, this dissertation focuses institutional status, central elements and professional development of social worker, and a brief historical trajectory of Social Service in the Judiciary System of Minas Gerais State. After all, this research was built upon presuppositions of conservative though and 1993 Ethical Code of Social Worker s values and principles